2022
DOI: 10.3390/su15010390
|View full text |Cite
|
Sign up to set email alerts
|

Grapevine Resistant Cultivars: A Story Review and the Importance on the Related Wine Consumption Inclination

Abstract: Pest and disease management in the grapevine sector has become difficult due to several instances (e.g., pathogen resistance, agrochemicals withdrawals). Therefore, viticulture switched to more environmentally friendly practices. On these bases, the most promising tool is the use of a resistant variety of grapes. Luckily, genetic and genomic selection have made great steps in accelerating plant breeding. In recent years, several resistant varieties of grape were created and the wine obtained began to grow. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…If the plant were in a state of decline, it would not be possible to make a proper comparison. This observation supports the higher sugar content in the control group, emphasizing the importance of canopy characteristics in facilitating photosynthesis, metabolite accumulation, and overall grapevine growth [38].…”
Section: Discussionsupporting
confidence: 80%
“…If the plant were in a state of decline, it would not be possible to make a proper comparison. This observation supports the higher sugar content in the control group, emphasizing the importance of canopy characteristics in facilitating photosynthesis, metabolite accumulation, and overall grapevine growth [38].…”
Section: Discussionsupporting
confidence: 80%
“…Specifcally, fndings from this study revealed that consumers prefer wine made with innovative rootstocks, followed by kaolin, PIWI, and PGRs, respectively. In terms of consumer preferences, wines derived from innovative rootstocks emerged as particularly attractive maybe because historical pest emergencies like phylloxera led producers to adopt new rootstocks, gradually encouraging consumer acceptance of wines stemming from this innovation [14]. Hence, consumers seemingly perceive this as a nonintrusive, climate-resilient technique.…”
Section: Discussionmentioning
confidence: 99%
“…Tese varieties are bred to have increased resistance to common vine diseases, thus reducing the need for frequent pesticide applications. Tis not only helps winegrowers cope with increased pest pressures due to climate change but also reduces the environmental impact of viticulture [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation